Structure-rheology relationships of protein-polysaccharide complexes at oil/water interfaces : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Physics at Biophysics and Soft Matter Group, School of Fundamental Science, Massey University - Ramamirtham, Sashikumar (Massey University, 2021)
The complexation of proteins with polysaccharides to form bio-complexes is being utilized in a variety of applications including food formulations, microencapsulation, protein separation and bioactive deliveries. Understanding the impact of these biomolecules on each other with discernment will not only improve our existing usages but also aid in devising newer applications. The duo of beta -lactoglobulin (beta -lg), a surface active globular whey protein, and pectin, a plant-derived polysaccharide, is the model protein-polysaccharide system of this study. Beta -lg and pectin have been reported to undergo complexation driven by electrostatic attraction leading to contrasting interfacial rheological properties depending on the fine structures of the polysaccharide. The aim of this thesis is to understand the role of fine structures of the polysaccharide in protein adsorption and the interfacial film formation. Given that beta -lg is the interfacially active molecule in this study, assemblies of beta -lg at dodecane/water interfaces at pHs 3 and 4, and at different conditions of ionic strength, salt type and temperature were studied. These parameters were tuned to vary the relative amounts of two native species, namely, monomer and its smallest aggregate, the dimer, while the interface was monitored using rheology and tensiometry. Unfolding of beta -lg dimers at the interface triggers the formation of disulfide linkages between the free thiol groups located at cys121 of the monomers. In this way, it is demonstrated here for the first time that beta -lg dimers are the smallest elastic network building unit of the protein. A higher concentration of dimers increases the final interfacial elastic strength of the network. The lack of the elastic film forming ability of beta -lg monomer is attributed to the absence of multiple free thiol groups. Moreover, beta -lg monomer exhibited minimal reduction in interfacial tension akin to a pure buffer solution. This fundamental relation between the quaternary structure of beta -lg and its subsequent interfacial network suggests a possible interfacial role in its biological function. Besides, these results will also be used as control for assessing the behaviors of beta -lg/polysaccharide complexes. In the next phase of this study, transient interfacial rheology of pre-mixed solutions of beta -lg and polysaccharides with different lengths and charge densities at pHs 3 and 4 are presented. It was found that, while the interfacial activity of beta -lg/pectin complexes is dictated by the amount of charge on the polysaccharide, the kinetics of the complexed beta -lg’s adsorption and its subsequent interfacial film formation is largely controlled by the contiguity of the charges on the polysaccharide molecule. Using subphase injection techniques, it is further shown that the structure of the beta -lg in the protein/polysaccharide complex prior to adsorption is the major contributor to the lag time duration before the onset of an elastic film formation. This is exemplified by the contrasting behaviors of beta -lg/pectin complexes with high polysaccharide charge density as compared to beta -lg/pectin complexes with low polysaccharide charge density, where the latter can be used as a one shot delivery system to obtain reinforced oil/water interfaces. It is further proposed that the mechanism by which a polysaccharide molecule reinforces beta -lg interfacial film is by concatenating multiple protein units and establishing cross-links in the aqueous subphase. The final phase of this study presents microrheology measurements of oil/water interfaces laden with beta -lg and beta -lg/polysaccharide complexes. Microrheology further ascertains the viscous nature of beta -lg monomer laden interfaces and the elastic nature of the interfaces with beta -lg dimers. In addition, the presence of heterogeneity in the entangled films made of beta -lg dimers in the form of confinements was also observed. A sharp transition was exhibited from an inelastic to elastic interface occurring around a surface dimer concentration of 56 ng/m2 at pH 3, 15 mM NaCl. Further, a slightly denser interface was observed for almost all the beta -lg/polysaccharide complexes at pH 4. The heterogeneity that was observed at dimeric interfaces was not seen for interfaces with beta -lg/polysaccharide complexes indicating the presence of the polysaccharide molecules beneath the interfacial film. On the whole, this thesis demonstrates the advantages of using of interfacial rheological techniques to tease out the structure-rheology relationships of biomolecules such as proteins and protein/polysaccharide complexes and thereby provide valuable insights about molecular manipulations.
Figures 1.1 & 1.2 are reproduced under a Creative Commons Attribution 3.0 Unported (CC BY 3.0) license. Figure 2.1 is reproduced under a Creative Commons Attribution 4.0 International (CC BY 4.0) license. Figures 1.4 (=de Kruif et al., 2004 Fig 3) & 1.6 (=Kubo et al., 2019 Fig 1.5) were removed for copyright reasons.
Listed in 2022 Dean's List of Exceptional Theses
Keywords: Proteins; Polysaccharides; Biomolecules; Interfaces (Physical sciences); Dean's List of Exceptional Theses; 510501 Biological physics